The role ofhousing in the ratrdom events ofthe phenomenon ofvisual poflution Case study ’,Um alwarid " in Al_Jadirya quorter. - MALAWISH, LOUAY Taha; Shamma, Zainab Salman (Iraqi Journal of Architecture and Planning, 2018)